2021
DOI: 10.1186/s12889-021-12156-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of an app-based child unintentional injury prevention intervention for caregivers of rural Chinese preschoolers: protocol for a cluster randomized controlled trial

Abstract: Background Compared to urban children, children living in rural areas of most countries, including China, are at higher risk of suffering unintentional injuries. Most proven injury prevention interventions, however, are rarely implemented in rural China due to lack of resources. Mobile health interventions are low-cost and easy-to-implement, facilitating implementing injury prevention in resource-limited areas (e.g., rural areas). This study is designed and implemented to examine the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A main advantage of our intervention is that it is relatively easy and low cost to administer. Globally, educational interventions for parents are becoming more feasible, with more mobile applications on unintentional injury prevention being developed 36–38. Some unintentional injuries in our study showed more significant reductions in the PPS analysis.…”
Section: Discussionmentioning
confidence: 59%
“…A main advantage of our intervention is that it is relatively easy and low cost to administer. Globally, educational interventions for parents are becoming more feasible, with more mobile applications on unintentional injury prevention being developed 36–38. Some unintentional injuries in our study showed more significant reductions in the PPS analysis.…”
Section: Discussionmentioning
confidence: 59%